2019
DOI: 10.14260/jemds/2019/581
|View full text |Cite
|
Sign up to set email alerts
|

Awareness about Consequence of Teenage Pregnancy

Abstract: BACKGROUND In a developing country like India, due to certain traditional customs, there are girls who become pregnant due to early marriage. There are multiple complications which could occur to the mother who has become pregnant at an adolescent age and to the foetus too. Various factors like educational status, religion, marital status, occupation, and type of family have an influence on this awareness. It also depends on the source of knowledge, respondents age of getting pregnant, knowledge about the cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…In a study by Siddharth A.R. et al ,[ 13 ] it was observed that low knowledge about contraceptive use was one of the common causes of getting pregnant at an early age and Oringanje C. et al .’s[ 14 ] study also showed a similar result. A qualitative study by Krugu JK et al .…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Siddharth A.R. et al ,[ 13 ] it was observed that low knowledge about contraceptive use was one of the common causes of getting pregnant at an early age and Oringanje C. et al .’s[ 14 ] study also showed a similar result. A qualitative study by Krugu JK et al .…”
Section: Discussionmentioning
confidence: 99%
“…The high rate of teenage pregnancy, defined as occurring before the age of 19 (1), threatens the futures of many teenage girls in South Africa and Southern African Development Region (2). They risk serious health, socio-economic and educational challenges (3,4), including the early termination of schooling due to policy, social norms or material conditions (5).…”
Section: Introductionmentioning
confidence: 99%
“…In some cultures, pregnancy and childbearing increases the probability of marriage. In developing countries, one in three women aged 20-24 married before the age of 18, a third of whom married before the age of 15 (5).…”
Section: Introductionmentioning
confidence: 99%